Autologous Deciduous Tooth-Derived Material for Alveolar Ridge Preservation: A Clinical and Histological Case Report - Elio Minetti; Silvio Taschieri; Stefano Corbella (Case Reports in Dentistry)
The management of the alveolar socket is fundamental to create conditions that would allow the positioning of dental implants in the same site, when required. A number of biomaterials were described in scientific literature to be used for alveolar socket preservation immediately after tooth extraction: autogenous grafts, allograft (of various origin), and synthetic products. Among the autogenous biomaterials, some authors proposed the use of autogenous dentin and/or enamel, retrieved from teeth, adequately managed, and purified. The present case report with two-year follow-up shows one case of alveolar socket preservation by using tooth graft material that was subsequently treated with one implant-supported rehabilitation in the same site. The paper presents clinical and histological outcomes and confirms the feasibility of adopting such autogenous biomaterial in standard procedures.